A prototype fatigue test for slab track subjected to the coupling action of wheel load, temperature variation, and water erosion. (May 2019) - Zhao, Pingrui; Ding, Chenxu; Guo, Likang; Zhang, Yuan'ai; Liu, Xueyi
Slab track is commonly used for high-speed railways in China. During its service life, the performance of the slab track may be affected by repeated wheel loading, temperature variation, and water erosion. In this study, a prototype fatigue test for the slab track was carried out during the winter season in a severely cold region of northeast China, considering the coupled effects of wheel load, temperature change, and water erosion. A loading vehicle configured with eccentric vibrator wheels was used to apply repeated wheel loading. The slab track system was heated and/or cooled to produce a temperature gradient consistent with the statistical characteristics of a real track system. Water erosion was also applied. The results show that the fatigue damage to the main structure of the slab track was less, even after 18.7 million cycles of wheel load under a severe temperature gradient. However, the cement asphalt mortar under the track slab may deteriorate rapidly from the edge and corner of the track slab when some initial damage was already present.